2019
DOI: 10.1001/jamainternmed.2018.6197
|View full text |Cite
|
Sign up to set email alerts
|

Care Practices for Patients With Advanced Kidney Disease Who Forgo Maintenance Dialysis

Abstract: IMPORTANCE Although maintenance dialysis is a treatment choice with potential benefits and harms, little is known about care practices for patients with advanced chronic kidney disease who forgo this treatment. OBJECTIVE To describe how decisions not to start dialysis unfold in the clinical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
119
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 88 publications
(122 citation statements)
references
References 39 publications
3
119
0
Order By: Relevance
“…Either providers are not presenting conservative management as a viable treatment option or they are not conveying conservative management in a way that patients and their family members perceive it as such. In a qualitative study of documentation in electronic medical records, Wong et al 19 found that providers did not themselves perceive foregoing dialysis or conservative management as an acceptable option and thought that they had little to offer patients who did not accept dialysis. This was suggested in our study by the patient who recounted the nurse crying in response to his desire to forego dialysis.…”
Section: Discussionmentioning
confidence: 99%
“…Either providers are not presenting conservative management as a viable treatment option or they are not conveying conservative management in a way that patients and their family members perceive it as such. In a qualitative study of documentation in electronic medical records, Wong et al 19 found that providers did not themselves perceive foregoing dialysis or conservative management as an acceptable option and thought that they had little to offer patients who did not accept dialysis. This was suggested in our study by the patient who recounted the nurse crying in response to his desire to forego dialysis.…”
Section: Discussionmentioning
confidence: 99%
“…In none of the different clinical scenarios did patients' goals and values figured prominently in the decision‐making process . Nephrologists motivated to act in the best interests of patients failed to consider how dialysis damages what matters most to the patients …”
Section: Barriers To Sdm Implementationmentioning
confidence: 99%
“…Nephrologists motivated to act in the best interests of patients failed to consider how dialysis damages what matters most to the patients. 27 Poor listening may be the single most important barrier in the optimal implementation of SDM. Patients want physicians to listen to them as they have unique knowledge about their own body and symptoms, but in practice, clinicians interrupt patients after a median of 11 seconds.…”
Section: Barriers To Sdm Implementationmentioning
confidence: 99%
“…Even when patients with advanced CKD express wishes to pursue medical management, they may find resistance from their providers or difficulty accessing alternatives to dialysis. 20 Borrowing from decision-making frameworks for considering other forms of life-sustaining treatment such as cardiopulmonary resuscitation, 21 we can begin to shift our default approach in dialysis decision-making conversations from "offer dialysis" to "consider dialysis" or even "recommend against dialysis." In this way, we base our discussion of dialysis initiation on the likelihood and plausibility of providing benefit versus harm in the context of the patient's unique goals, rather than assuming that dialysis must always be offered.…”
Section: Revise the Default In Dialysis Decision Makingmentioning
confidence: 99%